Inovasi Supervisi Akademik Kepala Sekolah Terhadap Profesionalisme Guru di SDN Parsanga IV Kecamatan Kota Sumenep, Kabupaten Sumenep - Fifit Humairah; Ashari Ashari (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Based on the research results, it was found that the school principal's academic supervision innovation in improving teacher professionalism at SDN Parsanga IV Sumenep, namely by following up in the form of monitoring using CCTV and follow-up carried out with CCTV accompanied by feedback and reflection can increase teacher professionalism well. This academic supervision innovation was carried out because of obstacles and with the implementation of these innovations the obstacles could be overcome properly. Among the successes of the innovations in academic supervision carried out by the principal of SDN Parsanga IV is that these innovations can become the main driver of changes in teaching styles by teachers. Has a good impact on the relationship between the teacher and the principal, so that the increase in teacher professionalism can run as expected. Acceptance of innovation by teachers because in implementing this academic supervision innovation, teachers feel heard, valued, and involved in the development of academic supervision innovations, they tend to be more open to change and are happy to receive feedback and joint reflection to improve their professionalism in teaching.